Pengaruh Stress Kerja, Work Life Balance dan Konflik Peran Terhadap Kinerja Karyawan - Zaenha, Mochamad Abdi Redani; Kusuma, Kumara Adji; Abadiyah, Rifdah (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
With the increasing degree of human requirements over time, the economy is also evolving and changing. Accordingly, to obtain it, working becomes the main way for those in need of money. There are a lot of students who work and study concurrently. They encountered numerous challenges as a result of this circumstance, including role conflict (X3), stress (X1), and work-life balance (X2). With 110 respondents, the research population consisted of active management study program students at UMSIDA campus one, and the non-probability sampling technique was employed. Multiple linear regression is used in this data analysis with the aid of SPSS software. The study's findings demonstrated the influence of role conflict (X3), work-life balance (X2), and job stress (X1) on the performance of employees who studied at UMSIDA. This is shown by the F-count value of 56.240 with a significance of 0.000 (<0.05).